ESTIMATING SEASONAL PATTERNS OF FISHING FOR ANCHOVIES (Stolephorus Sp) LANDED AT PPI PAOTERE, MAKASSAR, SOUTH SULAWESI: AN APPROACH TO FISHING BUSINESS EFFICIENCY - Ridwan, Muhammad; Muhiddin, Amir Hamzah; Zainuddin, Mukti (Hasanuddin University, 2024)
The exploitation level of fish resources should be based on effectiveness, efficiency and business sustainability. One of the efforts to implement these three aspects is to understand the seasonal pattern or the best time to catch the fish target. The aim of this research was to estimate the pattern of the anchovy fishing season based on production data landed at PPI Paotere Makassar, South Sulawesi. Data is collected from the PPI and analyzed using the moving average techniques. Results showed that the seasonal pattern of anchovy fishing is estimated to increase in the transition season to the eastern season (IMP > 100%) and reach a peak in September (IMP = 134.74%). Descriptively, the fishing season, especially the peak season, was thought to occur because these fish are probably associated with optimum conditions for oceanographic parameters such as sea surface temperature, chlorophyll-a concentrations and surface current conditions. Information on anchovy fishing season patterns is really needed by marine fisheries managers, both government and private, in managing efforts to exploit fish resources wisely and sustainably.